2019
DOI: 10.15835/nbha47311437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Shading Rates on the Photosynthesis and Corm Weight of Konjac Plant

Abstract: To study the effects of shading level on the photosynthesis and corm weight of konjac plant, the chlorophyll fluorescence parameters, daily variation of relative electron transport rate (rETR), net photosynthetic rate (Pn), and corm weight of konjac plants under different treatments were measured and comparatively analyzed through covered cultivation of biennial seed corms with shade nets at different shading rates (0%, 50%, 70%, and 90%). The results showed that with the increase in shading rate, the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Compared with Fv/Fm, the rETR shows the actual photosynthetic electron transfer for the specific experimental condition. 39 Higher light intensities stimulated higher electron transfer, and the best CO 2 concentration for electron transfer also increased with the increase in light intensity. F o represents the combined results of the chlorophyll fluorescence yield and comprehensive light proton consumption rates (namely, PSII thermal dissipation and photochemistry).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Compared with Fv/Fm, the rETR shows the actual photosynthetic electron transfer for the specific experimental condition. 39 Higher light intensities stimulated higher electron transfer, and the best CO 2 concentration for electron transfer also increased with the increase in light intensity. F o represents the combined results of the chlorophyll fluorescence yield and comprehensive light proton consumption rates (namely, PSII thermal dissipation and photochemistry).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Compared with the ideal light intensity, both higher and lower light intensities exerted stress on the PSII primary photochemical reaction. Compared with Fv/Fm, the rETR shows the actual photosynthetic electron transfer for the specific experimental condition . Higher light intensities stimulated higher electron transfer, and the best CO 2 concentration for electron transfer also increased with the increase in light intensity.…”
Section: Resultsmentioning
confidence: 97%
“…It indicated that sowing Blue Bedder at T1 and sowing Mixed Bedding at T4 could improve the photosynthetic performance of plants, and the photosynthetic performance and fluorescence performance of Blue Bedder were significantly higher than that of Mixed Bedding. In addition, F v /F m is the maximum primary photochemical quantum efficiency of PSII and an important parameter of photochemical reaction, which reflects the potential maximum photosynthetic capacity of plants 26 . F v /F m of most higher plants ranged from 0.8 to 0.85, and when F v /F m decreased, it represented that the plants were under stress 27 29 .…”
Section: Discussionmentioning
confidence: 99%